2017
DOI: 10.1002/ecy.1755
|View full text |Cite
|
Sign up to set email alerts
|

Blown by the wind: the ecology of male courtship display behavior in orchid bees

Abstract: Many insects rely on chemical signals to transmit precise information on the location, identity, and quality of potential mates. Chemical signals are often broadcasted at sites with physical properties that maximize signal propagation and signal transmission. Male neotropical orchid bees (Euglossini) perch and display on vertical branches and tree trunks in the forest to expose volatile blends (perfumes) that they previously collected from their environment. Previous studies have shown that the chemical compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…), and cicadas (Bennet‐Clark and Young ) and chemical signals that are directionally transmitted through wind (Pokorny et al. ) or water flow (Atema ). Therefore, our results can be interpreted across multiple signal modalities, demonstrating that the need for signalers to behaviorally alter, position, and/or orient themselves or their signals relative to their intended receiver and environment, and these behaviors should closely coevolve with the directional aspects of their signals for optimal presentation and transmission through the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and cicadas (Bennet‐Clark and Young ) and chemical signals that are directionally transmitted through wind (Pokorny et al. ) or water flow (Atema ). Therefore, our results can be interpreted across multiple signal modalities, demonstrating that the need for signalers to behaviorally alter, position, and/or orient themselves or their signals relative to their intended receiver and environment, and these behaviors should closely coevolve with the directional aspects of their signals for optimal presentation and transmission through the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, some colorful ornaments are only observable due to specific behavioral manipulations, such as uncovering a colorful patch (e.g., lifting a wing and showing an underwing color patch; (Hansen and Rohwer 1986;Zanollo et al 2013), positioning the color patch toward the receiver (e.g., male Harbronattus jumping spiders ensuring they directly face a female throughout their courtship display; (Echeverri et al 2017), or repositioning various body parts to create a color-display not possible in a natural body position (e.g., superb bird-of-paradise, Lophorina superba; Laman and Scholes 2012). Thus, for many animals, behaviors are important to optimizing color presentations during displays and/or coloration is important to accentuating behavioral (Rosenthal 2007;Patricelli et al 2016), such as the directional acoustic signals of blackbirds (Larsen and Dabelsteen 1990;Patricelli et al 2007), treehoppers (Cocroft et al 2000), and cicadas (Bennet-Clark and Young 1998) and chemical signals that are directionally transmitted through wind (Pokorny et al 2017) or water flow (Atema 1995). Therefore, our results can be interpreted across multiple signal modalities, demonstrating that the need for signalers to behaviorally alter, position, and/or orient themselves or their signals relative to their intended receiver and environment, and these behaviors should closely coevolve with the directional aspects of their signals for optimal presentation and transmission through the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its likely importance in dispersing scents, the role of wind in orchid bee ecology is not well understood, although previous observers have noted temporary increases in orchid bee arrivals at baits after wind gusts [39]. Recent work has also shown that male orchid bees performing mating displays strongly prefer to orient on the downwind side of trees, presumably to maximize the dispersal of odor plumes [40]. However, to our knowledge, quantitative studies of the impacts of wind (or turbulence) on spatial or temporal variation in orchid bee abundance and visitation rates at scent sources have not been made.…”
Section: Introductionmentioning
confidence: 99%
“…Orchid bee males collect scents from floral and nonfloral sources to concoct a complex species-specific chemical "perfume" blend (Dressler, 1982;Eltz, Whitten, Roubik, & Linsenmair, 1999;Roubik & Hanson, 2004;Weber, Mitko, Eltz, & Ramírez, 2016;Zimmermann, Ramírez, & Eltz, 2009). The perfume is subsequently released during a stereotypical display behavior at perching sites (Pokorny et al, 2017). It is only in combination with perfume display behavior that mating occurs (Dodson, 1966;Kimsey, 1980;Pokorny et al, 2017;Stern, 1991;Zimmermann, Roubik, & Eltz, 2006).…”
mentioning
confidence: 99%
“…The perfume is subsequently released during a stereotypical display behavior at perching sites (Pokorny et al, 2017). It is only in combination with perfume display behavior that mating occurs (Dodson, 1966;Kimsey, 1980;Pokorny et al, 2017;Stern, 1991;Zimmermann, Roubik, & Eltz, 2006). Although the exact function of perfume bouquets is still unclear, they are most likely involved in sexual selection, presumably by enabling species-specific recognition or the discrimination of males within a species.…”
mentioning
confidence: 99%